Oil based variation impact on fuel consumption of four-stroke 125 cc engine - A.S. Ardiyanta; E.R. Putra (Dinamika Teknik Mesin, 2025)
Oil is one of the crucial components in the lubrication system of four-stroke engines, particularly in motorcycles. Generally, engine oil is categorized into mineral oil, semi-synthetic oil, and fully-synthetic oil. The purpose of this research is to examine the effect of different base oil types on fuel consumption. The research was conducted using an experimental method, with the independent variable being the type of base oil: mineral oil, semi-synthetic oil, and fully-synthetic oil. The dependent variable of this research is fuel consumption. A four-stroke engine with a 125 cc carburetor was used as the test engine. Each test was conducted in five times at an engine speed 2000 rpm. Data analysis was performed using repeated measures ANOVA. The results showed that the use of different base oil types had a significant effect on fuel consumption. The average of fuel consumption was approximately 9.4 mL/min for mineral oil, 8.2 mL/min for semi-synthetic oil, and 6.9 mL/min for fully-synthetic oil. It can be concluded, that fully-synthetic oil results in the lowest or the most efficient fuel consumption compared to both mineral and semi-synthetic oils.